Influence of inflow states of dynamic wake model on trim, rotor loads and control response of a helicopter in forward flight - Lokeswara Rao, V.; Rohin Kumar, M.; Venkatesan, C. (My University, 2015)
A crucial step in the design of rotorcraft is the prediction of oscillatory loads produced by the periodic aerodynamic environment of the helicopter rotor. These oscillatory loads cause vibrations in the helicopter. The vibrations normally pervade both the rotor and the airframe and can seriously degrade service life as well as ride qualities. Accurate prediction of helicopter oscillatory / dynamic loads and response requires the development of multidisciplinary comprehensive analysis program which combines structure, aerodynamic and inertial operators. In this study, one such comprehensive analysis model is described. The model includes elastic flap-lag-torsion and axial blade deformations, modified ONERA dynamic stall theory for airloads calculation, and Peters-He dynamic wake theory for inflow computation. In the present study the number of state variables representing the inflow are varied from 3 states to 45 states by increasing the number of harmonics and radial functions, and their effects on helicopter trim, rotor loads and control response are analysed. Results indicate that there is a clear redistribution of inflow with the increase in number of inflow states. In general there is an increase in the inflow from forward to the aft of the rotor disk with the increase in number of states. It is important to note that there is no significant change in the trim variables with the increase in number of inflow states. However with the inclusion of higher harmonic inflow states, the harmonic content increase in sectional loads and blade root loads. Higher inflow states are seen to affect helicopter control response to longitudinal input at high speeds.
Keywords: Dynamics